PENGARUH KETERAMPILAN PENGELOLAAN KELAS TERHADAP MOTIVASI BELAJAR DI SMA NEGERI 4 SUNGAI RAYA - Cici Andini; Achmadi Achmadi; Okianna Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research aims to determine the effect of classroom management skills on learning motivation of class X SMA Negeri 04 Sungai Raya. The research method used is descriptive with a correlational research form. The number of population in this study was 66 students. The results of this study indicate that there is a positive effect of classroom management skills on learning motivation of Class X students of SMA Negeri 04 Sungai Raya. This can be seen from the t count of 6.132 which shows the influence of the independent variable on the dependent variable. When compared with the t table at the 0.05 significance level of 1.998. The coefficient of determination from the results of this study shows the contribution of the influence of variable X to variable Y, namely class management skills on student learning motivation by 37%, while the rest is influenced by other factors that are not explained in this study. So the conclusion is that Classroom Management Skills Influence the Learning Motivation of Class X Students of SMA Negeri 04 Sungai Raya.Keywords: Classroom Management Skills, Learning Motivation